Crete & Mycenae (Irwindale, Calif Barr Entertainment, 1991)
Shows the archaelogical findings at Knossos and elsewhere on Crete, as well as Mycenae on the Greek mainland, in order to compare the cultural history of the Minoan civilization with that of Mycenae.
VHS format.
Music, Enno Dugend.
Keywords: Civilization, Mycenaean; Minoans; Crete (Greece) -- Antiquities